A machine learning method for predicting the probability of MODS using only non-invasive parameters. (December 2022) - Liu, Guanjun; Xu, Jiameng; Wang, Chengyi; Yu, Ming; Yuan, Jing; Tian, Feng; Zhang, Guang
Highlights: Only easily obtained noninvasive parameters were used for MODS prediction, allowing the model to be applied in pre-hospital first aid or battlefield environments. ML is better than traditional scoring method in predicting MODS and mortality in ICU. The optimal features were selected for modeling to balance the number of parameters and predictive performance, which can make the model easily be integrated in emergency equipment and provide more robust advice in pre-hospital first-aid. ABSTRACT: Objectives: Timely and accurate prediction of multiple organ dysfunction syndrome (MODS) is essential for the rescue and treatment of trauma patients However, existing methods are invasive, easily affected by artifacts and can be difficult to perform in a pre-hospital setting. We aim to develop prediction models for patients with MODS using only non-invasive parameters. Method: In this study, records from 2319 patients were extracted from the Multiparameter Intelligent Monitoring in Intensive Care Ⅲ database (MIMIC Ⅲ), based on the sequential organ failure assessment (SOFA) score. Seven commonly used machine learning (ML) methods were selected and applied to develop a real-time prediction method for MODS based on full parameters (laboratory parameter. drug and non-invasive parameters, 57 parameters in total) and non-invasive parameters only (17 parameters) and compared with four traditional scoring systems. Results: The prediction results using LightGBM (LGBM) and Adaboost based on the full parameter modeling were 0.959 for area under receiver operating characteristic curve (AUC), outperforming four traditional scoring systems. The removal of 40 parameters and retaining of 17 non-invasive parameters decreased the AUC value of LGBM by 0.015, which still outperformed all traditional scoring systems. Conclusions: A real-time and accurate MODS prediction method was developed in this paper based on non-invasive parameters by comparing the performance of four ML methods, which proved to be superior to the traditional scoring systems. This method can help medical staff to diagnose MODS as soon as possible and can improve the survival rate of patients in a pre-hospital setting.